Strategi Untuk Meningkatkan Kreativitas Siswa Melalui Kewirausahaan Pendidikan: Tinjauan Literatur - Khaerani; Wahira; Romansyah Sahabuddin; Hasnawati (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2024)
This article is entitled "Strategies for Increasing Student Creativity Through Entrepreneurship Education: A Literature Review" which examines the role of entrepreneurship education in increasing student creativity. This article discusses several strategies that can be applied in education, such as project and problem-based approaches, entrepreneurship training, and the use of technology. This research emphasizes that entrepreneurship not only teaches business skills but also develops creative and innovative thinking abilities. In addition, this article also identifies challenges in implementing entrepreneurship education, including limited resources and lack of teacher training